Solvent-Free, Base-Free Microwave-Mediated Iridium-Catalyzed N-Alkylation of Amides with Alcohols - Apsunde, Tushar D.; Trudell, Mark L. (Synthesis, 2014)
Solvent-free, base-free microwave-mediated (Cp*IrCl2)2-catalyzed conditions for the N-alkylation of amides with alcohols have been developed. A series of primary and secondary alcohols have been shown to produce high yields of N-alkyl arylamides and N-alkyl alkylamides.
Keywords: alcohol; alkylation; amide; iridium